Radical changes in Lewis acid catalysis: matching metal and substrate - Bleith, Tim Manuel; Deng, Qing-Hai; Wadepohl, Hubert; Gade, Lutz H. (Angewandte Chemie, 2016)
Whereas the stereochemical rigidity of the coordination sphere of boxmi/CuII catalysts is key to achieving high enantioselectivity in the electrophilic alkylation of β-ketoesters, this pathway is outperformed by a radical process for the corresponding catalytic transformation of oxindoles, giving rise to racemic products. For the corresponding ZnII catalysts, the selectivity in the latter process is outstanding despite the greater plasticity of the coordination shell. This reaction was thus developed into a highly useful synthetic method, which enabled the conversion of wide range of substrates with high yields and enantioselectivities.
Gesehen am 15.12.2022